Seroprevalence of Hepatitis C Virus among Risk Groups in MosulCity - Hashem Saddon, Israa; Ibraheem Salih, Nadia (Tikrit Journal of Pharmaceutical Sciences, 2023)
Cross sectional study of 200 blood donors and other risk groups were conducted in Mosul city. The prevalence of anti-HCV antibodies was (5.5%). Anti-HCV positivity was found to be more common in male at the age group of < l0 years. History of blood transfusion was observed as a common risk factor related to anti-HCV positivity. History of past and present signs that are related to anti-HCV positive were, (72.7%) of cases were suffered front upper abdominal discomfort , (54.5%) of cases lvere suffered from jaundice, (54.5%) of cases u'ere suffered from loss of appetite, (27.2%) of cases were suffered from arthralgia, (18.1%) of cases w'ere suffered from skin rash.